Emotional intelligence and consumer decision-making styles: the mediating role of brand trust and brand loyalty - George Kankam; Isaac Tetteh Charnor (Future Business Journal)
Abstract This paper brings to light emotional intelligence’s impact on consumer decision-making styles during purchases. We show how brand trust (BT) and brand loyalty (BL) act as mediators between emotional intelligence (EI) and decision-making styles. We further indicate how consumers rely on emotional intelligence (EI) when purchasing products or services based on specific decision-making styles and patterns. We examine this issue by selecting customers who shop at the Accra and West Hills Malls. Seven hundred and fifty (750) respondents from the two selected malls comprised the study’s sample size. The respondents were chosen using the simple random and accidental/convenient sampling approach. The study hypotheses were examined using cross-sectional survey data. We use confirmatory factor analysis and structural equation modeling to analyze the data. We exhibit reliable information that emotional intelligence mediates the relationship between BT and BL, while the relationship between brand trust and brand loyalty is more strongly mediated at higher levels of EI. The result indicates a partial mediation between emotional intelligence and decision-making style through brand loyalty. This paper aims to increase knowledge on the importance of emotional intelligence from the perspective of customers through decision-making styles.